PERAN BIMBINGAN DAN KONSELING UNTUK MENGHADAPI GENERASI Z DALAM PERSPEKTIF BIMBINGAN DAN KONSELING PERKEMBANGAN - Caraka Putra Bakti; Nindiya Eka Safitri (Universitas Muria Kudus, 2017)
Z generation are people who were born in the period from 1995 until 2010. This generation has a high intensity of use of information and communication technology. They need to be equipped with critical thinking, innovative thinking, problem solving and social interaction skills. Therefore, the school has a responsibility in this regard through learning activities. Beside the learning activities, counseling and guidance for the development of the Z generation is needed. Guidance and counseling services for the Z generation should use techniques and media based on information technology and communication to deliver a message to the students. The technique can be used be used to stimulate skills are discussions, focus group discussions, problem solving and simulation games, as well as their e-counseling service or cyber counseling. The media used can be videos, movies, Macromedia Flash, and so on. These efforts need to be complemented by collaboration with parents, schools, subject teachers, homeroom, and agencies or institutions or companies engaged in the field of information and communication technology.